2021
DOI: 10.5194/wes-6-1291-2021
|View full text |Cite
|
Sign up to set email alerts
|

Design procedures and experimental verification of an electro-thermal deicing system for wind turbines

Abstract: Abstract. There has been a substantial growth in the wind energy power capacity worldwide, and icing difficulties have been encountered in cold climate locations. Rotor blade icing has been recognized as an issue, and solutions to mitigate accretion effects have been identified. Wind turbines are adapting helicopter rotor and propeller ice protection approaches to reduce aerodynamic performance degradation related to ice formation. Electro-thermal heating is one of the main technologies used to protect rotors … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Anti-icing was identified as the preferred strategy when ambient temperatures were above −5 • C, and the system cost was no higher than 2% of the turbine's capital. Gezt et al [32] designed an efficient anti-icing system for wind turbines by combining modeling and experimental testing. Experimental tests showed that accumulated ice needs to reach a certain minimum thickness to break away at a given available power.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-icing was identified as the preferred strategy when ambient temperatures were above −5 • C, and the system cost was no higher than 2% of the turbine's capital. Gezt et al [32] designed an efficient anti-icing system for wind turbines by combining modeling and experimental testing. Experimental tests showed that accumulated ice needs to reach a certain minimum thickness to break away at a given available power.…”
Section: Introductionmentioning
confidence: 99%
“…As a renewable energy with great development potential, wind energy plays a key role in global energy. Wind turbines are mostly built in high altitudes and cold regions to maximize the energy utilization degree, which makes it inevitable that wind turbine blades will face the problem of ice coverage. The formation and accumulation of ice seriously affect the efficiency and lifetime of wind turbines and may even pose a potential threat to the safety of surrounding buildings and residents. , Therefore, how to efficiently and quickly remove accumulated ice on wind turbine blades has become a critical issue. The existing active deicing technologies mainly include chemical deicing, , mechanical deicing, thermal deicing, , etc., but these deicing technologies generally suffer from the disadvantages of environment pollution, low efficiency, and high energy consumption …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Therefore, how to efficiently and quickly remove accumulated ice on wind turbine blades has become a critical issue. The existing active deicing technologies mainly include chemical deicing, 10,11 mechanical deicing, 12 thermal deicing, 13,14 etc., but these deicing technologies generally suffer from the disadvantages of environment pollution, low efficiency, and high energy consumption. With the development of anti-icing/deicing technology, passive anti-icing surfaces quickly entered the vision of scholars, such as a superhydrophobic surface, 15−18 a slippery liquidinfused porous surface, 19−21 and an icephobic polymer with low interfacial toughness.…”
Section: Introductionmentioning
confidence: 99%